Common Inflammatory Mechanisms in COVID-19 and Parkinson’s Diseases: The Role of Microbiome, Pharmabiotics and Postbiotics in Their Prevention - Danilenko V; Devyatkin A; Marsova M; Shibilova M; Ilyasov R; Shmyrev V (Dove Medical Press, 2021)
Valery Danilenko,1 Andrey Devyatkin,2 Mariya Marsova,1 Madina Shibilova,3 Rustem Ilyasov,1 Vladimir Shmyrev4 1Vavilov Institute of General Genetics, Russian Academy of Sciences, Moscow, Russia; 2Central Clinical Hospital with a Polyclinic CMP RF, Moscow, Russia; 3Polyclinic No. 1 CMP RF, Moscow, Russia; 4Central State Medical Academy CMP RF, Moscow, RussiaCorrespondence: Rustem Ilyasov Email apismell@hotmail.comAbstract: In the last decade, metagenomic studies have shown the key role of the gut microbiome in maintaining immune and neuroendocrine systems. Malfunction of the gut microbiome can induce inflammatory processes, oxidative stress, and cytokine storm. Dysfunction of the gut microbiome can be caused by short-term (virus infection and other infectious diseases) or long-term (environment, nutrition, and stress) factors. Here, we reviewed the inflammation and oxidative stress in neurodegenerative diseases and coronavirus infection (COVID-19). Here, we reviewed the renin-angiotensin-aldosterone system (RAAS) involved in the processes of formation of oxidative stress and inflammation in viral and neurodegenerative diseases. Moreover, the coronavirus uses ACE2 receptors of the RAAS to penetrate human cells. The coronavirus infection can be the trigger for neurodegenerative diseases by dysfunction of the RAAS. Pharmabiotics, postbiotics, and next-generation probiotics, are considered as a means to prevent oxidative stress, inflammatory processes, neurodegenerative and viral diseases through gut microbiome regulation.Keywords: renin-angiotensin-aldosterone system, gut microbiome, coronavirus infection, COVID-19, neurodegenerative diseases, inflammatory processes, oxidative stress, pharmabiotics, probiotics, postbiotics, symbiotics, Lactobacillus